Incidence of the Triple Whammy Phenomenon among Cardiovascular diseases patients in Saudi Arabia and awareness among healthcare professionals - Mohammad Bonyan Alsobaie; Mohammad Bonyan Alsobaie; Lubna Alsheikh (Frontiers in Nephrology)
Cardiovascular diseases are a leading cause of mortality in Saudi Arabia, accounting for approximately 42% of deaths. The “triple whammy” phenomenon—which combines angiotensin-converting enzyme inhibitors or angiotensin receptor blockers, diuretics, and non-steroidal anti-inflammatory drugs—increases the risk of acute kidney injury, particularly in hypertensive patients. This study, which was conducted in small-scale hospitals in Jeddah from 2017 to 2022, assessed the incidence of the triple whammy phenomenon and the awareness of healthcare professionals of this condition. Of 5,654 patient records, 1,899 met the inclusion criteria, with 2.7% experiencing the triple whammy. A survey of 56 healthcare professionals revealed 75% unawareness, with pharmacists and dentists being the most affected. Access to over-the-counter non-steroidal anti-inflammatory drugs and gaps in training likely drive the incidence and awareness deficits. This phenomenon can lead to acute kidney injury, with mortality rates as high as 50%–80% in critically ill patients, and imposes significant costs, representing 5% of hospital budgets and 1% of the overall health expenditure. Interventions including education, pharmacist roles, and non-steroidal anti-inflammatory drug regulation are proposed. Limitations include the small-scale focus and the low survey sample, necessitating national studies to accurately measure incidence and to improve patient safety.